Detection of Staphylococcus aureus, Streptococcus agalactiae and Escherichia coli in Brazilian mastitic milk goats by multiplex-PCR - Machado, Gustavo P.; Silva, Rodrigo C.; Guimarães, Felipe F. [UNESP]; Salina, Anelise [UNESP]; Langoni, Hélio [UNESP] (FapUNIFESP (SciELO), 2018)
This study evalueted the prevalence of Staphylococcus aureus, Streptococcus agalactiae and Escherichia coli in milk samples from 257 goats (513 half-udders) and ten bulk tanks, from ten dairy goat farms of São Paulo State, Brazil, by multiplex-PCR. The samples were screened by microbiological culture (gold-standard), and tested by different multiplex-PCR protocols for the detection of each bacterium. A total of 178 half-udders resulted positive by microbiological culture, with coagulase-negative staphylococci (70%), S. aureus (13.5%), S. intermedius (7.9%), and Enterobacteriaceae (4%) the prevalent pathogens. In other way, multiplex-PCR detected 173 pathogens in 151/523 (28.9%; CI95% 25.2-32.9%) milk samples 144/513 (28.1%) half-udders and 7/10 (70%) bulk tanks, with E. coli (86/162, 51.9%) and S. aureus (50/162, 30.9%) the prevalent ones in half-udders, and S. aureus (6/10, 60%) and E. coli (4/5, 36.4%) in bulk tanks. Multiplex-PCR showed a high performance for the detection of three bacteria at a time in mastitic goat milk direct from half-udders or bulk tanks. Thus, this multiplex-PCR protocol proved to be an adequate tool for the identification of the most common mastitis pathogens, independent of their phenotypic characteristics in the diagnosis of clinical mastitis in goats, allowing a continuous and better vigilance and monitoring the herd, being included in quality programs.
Keywords: Bulk tanks; Escherichia coli; Goats; Mastitis; Microbiological culture; Milk; Multiplex-PCR; Staphylococcus aureus; Streptococcus agalactiae